Respuesta :
Answer:
[tex](\frac{1}{2},0),(\frac{3}{2},0)[/tex]
Step-by-step explanation:
The vertex form of a parabola is given by:
[tex]y=a(x-h)^2+k[/tex], where V(h,k) is the vertex of the parabola.
The given parabola has vertex (1,1).
This implies that: [tex]h=1,k=1[/tex].
Put these values into the vertex form equation.
[tex]\implies y=a(x-1)^2+1[/tex]
The y-intercept of this parabola is: (0,-3).
This point lies on the parabola hence it must satisfy its equation.
[tex]\implies -3=a(0-1)^2+1[/tex]
[tex]\implies -3=a(-1)^2+1[/tex]
[tex]\implies -3=a(1)+1[/tex]
[tex]\implies -3=a+1[/tex]
[tex]\implies -3-1=a[/tex]
[tex]\implies -4=a[/tex]
The equation now becomes
[tex]\implies y=-4(x-1)^2+1[/tex]
To find the x-intercept, put y=0 into the equation:
[tex]\implies -4(x-1)^2+1=0[/tex]
[tex]\implies -4(x-1)^2=-1[/tex]
Divide through by -4.
[tex]\implies \frac{-4(x-1)^2}{-4}=\frac{-1}{-4}[/tex]
[tex]\implies (x-1)^2=\frac{-1}{-4}[/tex]
[tex]\implies (x-1)^2=\frac{1}{4}[/tex]
Take plus or minus square root of both sides.
[tex]\implies x-1=\pm \sqrt{\frac{1}{4}}[/tex]
[tex]\implies x-1=\pm \frac{1}{2}[/tex]
[tex]\implies x=1\pm \frac{1}{2}[/tex]
[tex]\implies x=1-\frac{1}{2}[/tex] or [tex]\implies x=1+ \frac{1}{2}[/tex]
[tex]\implies x=\frac{1}{2}[/tex] or [tex]\implies x=1 \frac{1}{2}[/tex]
Therefore the x-intercepts are:
[tex](\frac{1}{2},0),(\frac{3}{2},0)[/tex]
To the nearest hundredth, we have [tex]0.50,0),(1.50,0)[/tex]